Zero-valent iron mediated degradation of ciprofloxacin - Assessment of adsorption, operational parameters and degradation products - Perini, João Angelo de Lima; Silva, Bianca Ferreira da; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier, 2014)
The zero-valent iron (ZVI) mediated degradation of the antibiotic ciprofloxacin (CIP) was studied under oxic condition. Operational parameters such as ZVI concentration and initial pH value were evaluated. Increase of the ZVI concentration from 1 to 5 g L−1 resulted in a sharp increase of the observed pseudo-first order rate constant of CIP degradation, reaching a plateau at around 10 g L−1. The contribution of adsorption to the overall removal of CIP and dissolved organic carbon (DOC) was evaluated after a procedure of acidification to pH 2.5 with sulfuric acid and sonication for 2 min. Adsorption increased as pH increased, while degradation decreased, showing that adsorption is not important for degradation. Contribution of adsorption was much more important for DOC removal than for CIP. Degradation of CIP resulted in partial defluorination since the fluoride measured corresponded to 34% of the theoretical value after 120 min of reaction. Analysis by liquid chromatography coupled to mass spectrometry showed the presence of products of hydroxylation on both piperazine and quinolonic rings generating fluorinated and defluorinated compounds as well as a product of the piperazine ring cleavage.
Keywords: ferro metálico; fármacos; Metallic iron; Antibiotic; Iron dissolution; Adsorption; Defluorination